Submarine topography : vicinity of Bogoslof Island, Bering Sea / American Geographical Society - American Geographical Society of New York (American Geographical Society, 1937)
Includes ancillary location map. "Contours by Paul A. Smith (1937) from hydrography by party of Discoverer, H.B. Campbell, commanding (1935), U.S. Coast and Geodetic Survey." Color 1:440,000